The synergy between the athlete's functional systems and their training regimen is essential for achieving peak athletic performance - Khubbiev, S. Z.; Kostromin, O. V.; Zinovyev, N. A.; Alekseeva, N. V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to recognize the holistic approach to sports training, viewing the athlete's body as a unified and interconnected system.